Climatologia da precipitação do Rio Grande do Sul baseado em quatro esquemas convectivos do modelo climático regional RegCM3 - Guerra, Viviane da Silva (2012)
This paper presents the climatology of precipitation for the state of Rio Grande do Sul using the regional climate model RegCM3, 3rd version of the model. Four 30- year Climatologies were carried for the interval from 1975 to 2005 for the four convective schemes present in the model, Grell (1993) that has two locks, Arakawa and Schubert (1974) and Frisch and Chappell (1980), the modified Kuo by Anthes (1977) and Emanuell (1991). For each convective scheme were made four Climatologies one for each season: Summer, Autumn, Winter and Spring. From real data drawn from various sources and compiled by Liebmann and Allured, (2005), quarterly Climatologies were developed with real data (Observed) making it possible to analyze the sensitivity of the convective schemes through the Simulated Climatologies by RegCM3. The work also presents statistical analyzes to evaluate the performance of each convective scheme relating to the pattern of precipitation found in Climatologies of real data and also the climatological distribution variability, climatological distribution frequency and climatological precipitation anomalies .To analyze the distribution were evaluated daily average rainfall and maximum daily rainfall daily maximum minimum. To evaluate the dispersion between the observed and simulated values, were made measured dispersion and correlation with a significance level of 99%, the calculus of quantiles, standard deviation, IQR, RMSE and it was possible to estimate with higher degree of certainty which convective scheme can get closer to the observed climatology.